2015
DOI: 10.1074/jbc.m115.637603
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 1 and Sarcolipin Are Required to Maintain Optimal Thermogenesis, and Loss of Both Systems Compromises Survival of Mice under Cold Stress

Abstract: Background:The mechanisms underlying UCP1-independent thermogenesis are not well understood. Results: Loss of both SLN and UCP1 results in compromised thermogenic ability and severe sensitivity to acute cold. Conclusion: Sarcolipin-mediated thermogenesis is required for optimal thermogenesis and is up-regulated in the absence of UCP1. Significance: Sarcolipin is a crucial contributor to thermogenesis and energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 46 publications
8
114
0
Order By: Relevance
“…Moreover, the ability to recruit SLN/SERCA-mediated muscle-based NST without significantly affecting muscle maturation and function will be favorably selected for, specifically in non-tropical climates where temperature and food availability dramatically fluctuate seasonally. Recent studies from our lab further show that SLN increases fatigue resistance of muscle while increasing energy expenditure and contributes to thermogenesis (Maurya et al, 2015;Rowland et al, 2015;Sopariwala et al, 2015). Collectively, these findings along with our data suggest that SLN is an important marker of muscle-based thermogenesis.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, the ability to recruit SLN/SERCA-mediated muscle-based NST without significantly affecting muscle maturation and function will be favorably selected for, specifically in non-tropical climates where temperature and food availability dramatically fluctuate seasonally. Recent studies from our lab further show that SLN increases fatigue resistance of muscle while increasing energy expenditure and contributes to thermogenesis (Maurya et al, 2015;Rowland et al, 2015;Sopariwala et al, 2015). Collectively, these findings along with our data suggest that SLN is an important marker of muscle-based thermogenesis.…”
Section: Resultssupporting
confidence: 65%
“…In mice, brown adipose tissue (BAT) has been implicated as a major contributor to NST (Cannon and Nedergaard, 2004). However, recent studies by others and by us have shown that apart from shivering, skeletal muscle is also an important site of NST (Bal et al, 2012;Rowland et al, 2015;McKay et al, 2013;Louzada et al, 2014). We have demonstrated that skeletal muscle-based NST is largely mediated by a sarcoplasmic reticulum (SR) membrane protein called sarcolipin (SLN) (Bal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that mice lacking SLN were cold-sensitive, indicating a role of SLN in muscle-based NST (13). In addition, we showed that cold acclimatization of UCP 1 knockout mice (UCP 1-KO) up-regulated SLN expression in skeletal muscles, suggesting that muscle thermogenesis is recruited to a greater extent when BAT function is lost (14). Furthermore, cold adaptation studies using neonatal mice firmly suggest that muscle serves as a site of thermogenesis beyond shivering (23).…”
mentioning
confidence: 73%
“…20,21). Recently, we reported that modulation of SER Ca 2ϩ cycling by sarcolipin (SLN) in skeletal muscle plays an important role in NST (13,14,(22)(23)(24). Our data indicated that binding of SLN to sarcoendoplasmic reticulum Ca 2ϩ ATPase (SERCA) uncouples ATP hydrolysis from its Ca 2ϩ uptake function, leading to futile Ca 2ϩ cycling and heat production (22,25).…”
mentioning
confidence: 98%
See 1 more Smart Citation